Effect of perioperative levosimendan administration on postoperative N-terminal pro-B-type natriuretic peptide concentration in patients with increased cardiovascular risk factors undergoing non-cardiac surgery: protocol for the double-blind, randomised, placebo-controlled IMPROVE trial. Issue 1 (21st January 2022) - Reiterer, Christian; Kabon, Barbara; Taschner, Alexander; Adamowitsch, Nikolas; Graf, Alexandra; Fraunschiel, Melanie; Horvath, Katharina; Kuhrn, Melanie; Clement, Theresa; Treskatsch, Sascha; Berger, Christian; Fleischmann, Edith
Abstract : Introduction: Elevated N-terminal pro-brain natriuretic peptide (NT-pro-BNP) after non-cardiac surgery is a strong predictor for cardiovascular complications and reflects increased myocardial strain. NT-pro-BNP concentrations significantly rise after non-cardiac surgery within the first 3 days. Levosimendan is a potent inotropic drug that increases calcium sensitivity to cardiac myocytes, which results in improved cardiac contractility that last for approximately 7 days. Thus, we will test the effect of a pre-emptive perioperative administration of levosimendan on postoperative NT-pro-BNP concentration as compared with the administration of a placebo in patients undergoing moderate-risk to high-risk major abdominal surgery. Methods and analysis: We will conduct a double-blinded prospective randomised trial at the Medical University of Vienna, Vienna, Austria (and potentially a second centre in Germany), including 230 patients at-risk for cardiovascular complications undergoing moderate- to high-risk major abdominal surgery. Patients will be randomly assigned to receive a single dose of 12.5 mg levosimendan versus placebo after induction of anaesthesia. The primary outcome will be the postoperative maximum NT-pro-BNP concentration between both group within the first three postoperative days. Our secondary outcomes will be the incidence of myocardial ischaemia, myocardial injury after non-cardiac surgery and a composite of myocardial infarction and death within 30 days and 1 year after surgery between both groups. Our further secondary outcome will be stratification of NT-pro-BNP values according to previously thresholds to predict mortality of myocardial infarction after surgery. Ethics and dissemination: The study was approved by the Ethics Committee of the Medical University of Vienna on 14 July 2020 (EK 2187/2019). Written informed consent will be obtained from all patients a day before surgery. Results of this study will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT04329624 .